A new page on the road book of inorganic mercury in fish body – tissue distribution and elimination following waterborne exposure and post-exposure periods. Issue 3 (11th March 2015) - Pereira, Patrícia; Raimundo, Joana; Barata, Marisa; Araújo, Olinda; Pousão-Ferreira, Pedro; Canário, João; Almeida, Armando; Pacheco, Mário
<x xml:space="preserve">Abstract</x> Time-related accumulation/distribution of inorganic Hg upon exposure and post-exposure periods. Body compartments selected: gills, eye wall, lens, blood, liver, brain and bile.